Bagnards, orpailleurs et fonctionnaires du bassin du Maroni dans la Grande guerre - Virginie Brunelot; Arnauld Heuret (Criminocorpus)
Saint Laurent du Maroni was a penal town. It was the capital of France’s penal administration in the Maroni [along the Maroni river], a vast territory that was populated both by convicts and free citizens. The participation of this complex population in the First World War was integral to their citizenship and considered as evidencing a desire to defend the ‘Motherland’.During the conflict, the penal colony was severely impacted by the lack of food and material provisions and only returned to its regular operation in 1921. At the same time, economic activity based along the Maroni river such as gold mining and balata exploitation contributed to the war effort.